Epidemiology and Medication Utilization Pattern of Aortic Dissection in Taiwan: A Population-Based Study - Yeh, Ting-Yu (Medicine (Baltimore), 2015)
Acute aortic dissection (AD) is a catastrophic condition associated with a high rate of mortality. However, current epidemiological information regarding AD remains sparse. The objective of the present study was to investigate the current epidemiological profile and medication utilization patterns associated with aortic dissection in Taiwan. In this population-based study, we identified cases of AD diagnosed during 2005 to 2012 in the complete Taiwan National Health Insurance (NHI) Research Database. Patients with AD were identified using the International Classification of Disease, Ninth Revision (ICD-9) code 441.0, and surgical interventions were defined using NHI procedure codes. A total of 9092 individuals with a mean age of 64.4 ± 15.1 years were identified. The cases were divided into 3 groups: Group A included 2340 patients (25.74%) treated surgically for type A AD; Group B included 1144 patients (12.58%) treated surgically for type B AD, and Group C included 5608 patients (61.68%) with any type of AD treated with medical therapy only. The average annual incidence of AD was 5.6 per 100,000 persons, and the average prevalence was 19.9 per 100,000 persons. Hypertension was the most common risk factor, followed by coronary artery disease and chronic obstructive pulmonary disease. Within 1 year of AD diagnosis, 92% of patients were taking antihypertensive medication. Calcium channel blockers were the most frequently prescribed antihypertensive medication for long-term observation in Taiwan. The annual trends revealed statistically significant increases in the numbers and percentages of prevalence, incidence, and mortality. Changes in patients’ drug utilization in patterns were observed after AD diagnosis. Our study provides a local profile that supports further in-depth analyses in AD-affected populations.